Медіаосвіта та медіаграмотність: освітні процеси формування компетентностей - Безена, Іван Михайлович; Ващенко, Марина Іванівна (Протидія дезінформації в умовах російської агресії проти України: виклики і перспективи: тези доп. учасників міжн. наук.-практ. конф. (Анн-Арбор - Харків, 12-13 груд. 2023 р.), 2023)
The State Standard of Basic Secondary Education (2020) outlines life competences in the content of the New Ukrainian School: information and communication competence, confident, critical and responsible use of digital technologies for personal development and communication; ability to safely use information and communication tools in learning and other life situations, etc. The Russian-Ukrainian war and the reintroduction of Russia into the territory of an independent state have confirmed the special importance of the combat readiness of the Armed Forces of Ukraine to protect the sovereignty of the state, internal unity and resilience of citizens and their media literacy and media education, critical assessment of information and prevention of its spread. The current times of hybrid and aggressive confrontations, fake news and disinformation have determined the correctness of the Ukrainian state’s course aimed at deepening democratisation, openness, fighting corruption, and ensuring that the information disseminated about activities, processes and events is truthful and understandable. After all, the victory of democracy over authoritarianism depends on the above. That is why the mission of the educational environment is special: schools, colleges, higher education institutions.